2020
DOI: 10.1038/s41586-020-2810-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental drivers of megafauna and hominin extinction in Southeast Asia

Abstract: Southeast Asia has emerged as an important region for understanding hominin and mammalian migrations and extinctions. High-profile discoveries show Southeast Asia was home to at least five members of the genus Homo 1-3 . Significant turnover in Pleistocene megafauna is linked with these hominins or climate change 4 , although the region is often left out of discussions of megafauna extinctions. Establishing the environmental context of hominin evolution and its association with faunal changes have long been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 116 publications
4
76
0
1
Order By: Relevance
“…S7 ). They are consistent with the environmental reconstruction made by Louys and Roberts 11 . Our findings also question the relationship between the changes in the rainforest environment and the major turnover of earlier hominins ( H. erectus , Denisovans) in SE Asia before the arrival of H. sapiens.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…S7 ). They are consistent with the environmental reconstruction made by Louys and Roberts 11 . Our findings also question the relationship between the changes in the rainforest environment and the major turnover of earlier hominins ( H. erectus , Denisovans) in SE Asia before the arrival of H. sapiens.…”
Section: Discussionsupporting
confidence: 92%
“…During the Late Pleistocene, the Far East witnessed a major turnover of hominins with the extinction of the last H. erectus in Indonesia 8 , the likely presence of the last Denisovans in several parts of the continent 9 and eventually the replacement of all archaic groups following the arrival of Homo sapiens 10 . On a continental scale, it has been suggested that the shift from open habitats (mixed savannah and woodland) to rainforest habitats at the transition between the Middle Pleistocene and the Late Pleistocene triggered the decline of archaic hominins, unable to adapt to these new environments 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, our findings can be related to changes in subsistence strategies toward more frequent and systematic hunting of larger-sized bovids in these environments, in association with cognitive changes toward more complex weapons and coordinated group activity. The lithic, faunal, and isotopic records show an increase of such behaviors and ecosystems inhabited by Homo throughout the Middle Pleistocene that supports this interpretation [40][41][42][43] . The divergent pattern in Neanderthals and Pleistocene H. sapiens might be due to an already higher established brain size close to the physiological maximum during colonization of more northern latitudes (>40°; H. sapiens: mean = 1505 cm 3 , n = 37; Neanderthals: mean = 1398 cm 3 ; n = 25), while the other taxon either evolved in situ in these areas or had higher growth potential.…”
Section: Discussionmentioning
confidence: 61%
“…The underlying causes for the megafaunal extinction at the end of the Pleistocene are still debated and tend to focus on two primary issues, climatic/environmental change and anthropogenic activities, or some combination of these 3 – 7 . The current rate of population reduction and potential extinction of herbivores and carnivores in the wild is a major global ecological issue.…”
Section: Introductionmentioning
confidence: 99%